2019
DOI: 10.17261/pressacademia.2019.1047
|View full text |Cite
|
Sign up to set email alerts
|

Trade liberalization and economic growth: a panel data analysis for transition economies in Europe

Abstract: Purpose-In this study, the long-term and the short-term relationships between economic growth and trade liberalization for 13 transition countries in Europe were examined. Methodology-The dataset includes 303 observations from 1995 to 2016 for the variables of gross domestic product (GDP), export (EXP), import (IMP), gross fixed capital formation (GFCF), foreign direct investment (FDI) and human capital (HC). PLS Test, Pesaran ( 2004) CD-Test, Pesaran (2007) Unit Root Test, Swamy S Homogeneity Test conducted b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
1
6
0
3
Order By: Relevance
“…In addition, unlike other studies, they concluded that political rights and infrastructure are not important indicators of FDI inflows to Africa. In the study conducted by Erkisi and Ceyhan (2019) to investigate the relationship between trade liberalization and economic growth in transition economies, it was concluded that economic growth has an impact on FDI in the short-run, however it reduces the FDI in the long-run. In the research carried out by Erkişi (2018) to explore the causal relationship between FDI, trade openness and economic growth in Turkey, economic growth, export, and import were not found to be the granger cause of FDI.…”
Section: The Determinants Of Fdi: Empirical Literaturementioning
confidence: 99%
“…In addition, unlike other studies, they concluded that political rights and infrastructure are not important indicators of FDI inflows to Africa. In the study conducted by Erkisi and Ceyhan (2019) to investigate the relationship between trade liberalization and economic growth in transition economies, it was concluded that economic growth has an impact on FDI in the short-run, however it reduces the FDI in the long-run. In the research carried out by Erkişi (2018) to explore the causal relationship between FDI, trade openness and economic growth in Turkey, economic growth, export, and import were not found to be the granger cause of FDI.…”
Section: The Determinants Of Fdi: Empirical Literaturementioning
confidence: 99%
“…Liberalisasi perdagangan adalah penghapusan atau pengurangan pembatasan atau hambatan pada pertukaran barang bebas antar negara, dan memiliki sisi yang menarik karena beberapa penulis menganggap bahwa liberalisasi perdagangan memiliki dampak negatif pada pertumbuhan ekonomi dan kemiskinan, seperti menyebabkan perlambatan pertumbuhan (Greenaway, Leybourne, & Sapsford, 1997), kurang efektif dalam mendorong pertumbuhan (Yanikkaya, 2003), menyebabkan ketimpangan dan kemiskinan di negara-negara berkembang (Gavin, M., & Hausmann, 1998;Laursen, Thomas and Mahajan, 2005;Islam & Fatema, 2017 ). Beberapa penulis juga mempertimbangkan dampak keterbukaan ekonomi yang diikuti oleh liberalisasi perdagangan yang tidak didukung oleh bukti yang cukup jika dikaitkan dengan pertumbuhan suatu negara (Rodriguez & Rodrik, 2000;Shafaeddin, 2010;Wacziarg, R., & Welch, 2003;Erkisi & Ceyhan, 2019;Alamro, 2017). Disisi lain, beberapa penulis berasumsi bahwa pertumbuhan ekspor tidak dipengaruhi oleh liberalisasi perdagangan (Agosín, 1991;Clarke, R., & Kirkpatrick, 1992;Jenkins, 1996).…”
Section: Pendahuluanunclassified
“…Pada saat itu, ekonomi runtuh dan beberapa krisis utang di negara-negara berkembang secara signifikan melemah terhadap pengaruh proteksionis. Beberapa literatur empiris menunjukkan hubungan sebab-akibat yang kuat antara perdagangan dan pertumbuhan, serta dampak terhadap kemiskinan (Erkisi & Ceyhan, 2019;Alamro, 245 2017;Islam & Fatema, 2017;Fauzel, 2020;Koffi et al, 2018;Mahembe & Odhiambo, 2019;Sofjan,2018). Untuk alasan itu, banyak negara membuat kebijakan konseptual untuk melakukan era liberalisasi.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Adam Smith was the first to hold the belief that trade liberalization had an impact on economic growth. The fundamental views of economists like Hume, Smith, and Ricardo, who supported the School of Mercantilism and Classical Economics, served as the beginning point for the lengthy argument that has continued to this day on this idea (Ceyhan & Erkisi, 2019).…”
Section: Introductionmentioning
confidence: 99%